The cultural boundaries and representations linking Bejaia Al Hammadia and Tlemcen Ziania. - Meziane, Ahmed (Milev Journal of Research and Studies, 2022)
We seek through this paper to look at aspects Related to scientific cities Of the Maghreb,With its wide geographical boundaries.In which capitals emerged recognized by the kingdoms and states,And The scientists who came to it knew their value They seek reward from their sheikhs and scholars,We find Tiaret Rustemiya Passing through Bejaia Nasiriyah Right up to Tlemcen Ziania And other cities that witnessed a terrible intellectual and cultural life manifested in what the traveler noted,As well as the survival of the effects of the civilization we are talking about castles and royal palaces and even ancient mosques and angles blessed at the roots of history,And Bejaia remains present with its acclaimed history of many countries,Despite the struggle between the Hafsids and the Zayans over themThis is due to the historical and cultural momentum it has endured.